Acute Oral Toxicity Study Of Norfloxacin In Female Rats - R. RASHMI,; K. JAYAKUMAR,; M. NARAYANA SWAMY,; AVINASH BHAT, (International Journal of Pharma and Bio Sciences, 2012)
Acute oral toxicity study with norfloxacin was conducted in female wistar albino rats. The study was carried out as per Acute toxic class method (OECD 423). Three animals were used for each step. Norfloxacin was administered by oral gavage as a single dose at a dose rate of 50 mg/kg body weight to Group I, 300 mg/kg body weight to Group II, 2000 mg/kg body weight to Group III, 5000 mg/kg body weight to Group IV. All animals tested at 5000 mg/kg showed mortality. There was no mortality in other treated groups. The results of the study enunciated that LD50 for norfloxacin was >2000 mg/kg body weight in female rats.